Chapter Classical Tradition in Czech Renaissance and Baroque Literature - Kysučan, Lubor (Biblioteca di Studi Slavistici, 2020)
The study deals with the influence of the classical tradition on Czech literature of the Early Modern Period (Renaissance, Baroque). The article demonstrates this influence through examples of the use of selected motifs from ancient history in all of the main genres of the literature of that era: homily, legend, school drama, poetry and educational literature. The study also analyses the educational background of the authors and readers of the era and their attitude to ancient history; the ways of mediation and making use of ancient motifs in the literature; and the influence of ancient historiography on Renaissance and Baroque culture and interpretation of history.